STRATEGIC PLANNING FOR THE COMPUTER ENGINEERING PROGRAM IN THE CONTEXT OF INTERNATIONALIZATION AT XYZ UNIVERSITY - Arief Rachman; Utomo Sarjono Putro (LPPM STIE Muhammadiah Bandung, 2025)
An internationalization initiative at XYZ University’s Computer Engineering program, involving the establishment of an international class, has created a significant operational risk. A regulation mandating the transfer of 6 to 10 lecturers from the main program threatens to disrupt academic stability and teaching quality for its existing 300+ students. This research develops a strategic plan to address the lecturer transfer challenge. A mixed-method approach was employed. Internal analysis, through thematic analysis of stakeholder interviews, identified strengths such as digital readiness and industry partnerships, and weaknesses like lecturer availability issues. External analysis using PESTLE and Porter’s Five Forces identified opportunities, including IoT advancements, and threats such as higher education competition. These factors informed a SWOT analysis, which led to seven TOWS-generated strategies. The Analytic Hierarchy Process (AHP), with input from eight program stakeholders, was then used to prioritize these alternatives.The AHP results showed that “Strength” was the most critical decision criterion. The strategy SO1: “Utilize industry partnerships and digital readiness to deliver IoT–integrated hybrid learning, reducing lecturer dependency,” received the highest global priority (18.2%). The AHP model demonstrated good consistency (overall CR=0.03). This study concludes that implementing an IoT-integrated hybrid learning model is the most effective strategy for the Computer Engineering program to manage the lecturer transfer. The research provides an evidence-based SWOT-AHP framework for higher education institutions managing resources during internationalization, ensuring that expansion enhances rather than compromises core academic quality.